1996
DOI: 10.2514/3.792
|View full text |Cite
|
Sign up to set email alerts
|

Thermal contact conductance of selected polymeric materials

Abstract: The thermal conductivity and thermal contact conductance of several thermoplastic and thermosetting polymers have been studied over a range of interface pressures and temperatures. The temperature range for the thermal conductivity study varied from 10 to 100°C (50 to 212°F). The study showed that ultra high molecular weight (UHMW) polyethylene had the highest thermal conductivity through the range of temperatures and also had the highest thermal conductance values at an interface temperature of 20°C (68°F). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 10 publications
1
42
2
Order By: Relevance
“…Marotta and Fletcher 5 showed that the contact conductance at selected polymer-aluminum interfaces also did not follow the trend given by either the elastic or the plastic models for contact conductance. Furthermore, the results of Rhee et al, 8 and Narh and Sridhar 9 show that the contact conductance at conforming plastic-metal surfaces is of the order of 0.125-0.25 ϫ 10 5 W/m 2 -K, which is more than an order of magnitude lower than that reported by Marotta and Fletcher,5 for surfaces that were not specially prepared to be conforming. At such interfaces, the effect of the surface waviness is expected to be a dominant factor in determining the magnitude of contact conductance, 10 resulting in a departure from the established contact conductance models.…”
Section: Introductioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Marotta and Fletcher 5 showed that the contact conductance at selected polymer-aluminum interfaces also did not follow the trend given by either the elastic or the plastic models for contact conductance. Furthermore, the results of Rhee et al, 8 and Narh and Sridhar 9 show that the contact conductance at conforming plastic-metal surfaces is of the order of 0.125-0.25 ϫ 10 5 W/m 2 -K, which is more than an order of magnitude lower than that reported by Marotta and Fletcher,5 for surfaces that were not specially prepared to be conforming. At such interfaces, the effect of the surface waviness is expected to be a dominant factor in determining the magnitude of contact conductance, 10 resulting in a departure from the established contact conductance models.…”
Section: Introductioncontrasting
confidence: 40%
“…[5][6][7][8][9][10][11][12] Such interfaces are typically between materials of widely varying thermal conductivity. From the perspective of processing and product design applications, metals that are most likely to be used (steels, aluminum) have thermal conductivity in the range of 35-250 W/m-K. 13 Plastics, on the other hand, have thermal conductivity generally in the range of 0.1-0.4 W/m-K, 14 while thermal conductivity of elastomers are in the range 0.5-1.5 W/m-K. Seyed Yagoobi et al 15 studied the thermal contact conductance at a paper-metal interface and showed that the contact conductance was a function of the logarithm of the contact pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that the values of Table II are rather high as stated by Shridhar,20 who found that for PS the value of TCR is around 10 −4 m 2 K W −1 . Shridhar also noted that the value of TCR changes during the injection molding cycle and at the later stages of postfilling approaches the values found by Yu et al 18 Moreover, the values quoted by Marotta and Fletcher 19 were found to be rather high and this was attributed to the waviness of the surface of the samples used in that experimental study. Another problem with Eq.…”
Section: Application Of Pham's Equation In Injection Moldingmentioning
confidence: 55%
“…Measurements of TCR are summarized in Table II along with the calculated values for TCC. 18,19 From a design point of view the cooling channel and the mold should not present a lot of resistance in heat transfer. Table II shows that in some cases TCC is less than 500 W m −2 K −1 , which means that the mold-part resistance is the controlling factor.…”
Section: Application Of Pham's Equation In Injection Moldingmentioning
confidence: 99%
“…Material characteristics for the Al ux meter and the polymeric specimen are shown in Table 3 (Refs. [23][24][25].…”
Section: Sample Preparationmentioning
confidence: 99%